A first comparison of bone histomorphometry in extant domestic horses (Equus caballus) and a Pleistocene Indian wild horse (Equus namadicus). Issue 6 (18th June 2020) - ZEDDA, Marco; SATHE, Vijay; CHAKRABORTY, Prateek; PALOMBO, Maria Rita; FARINA, Vittorio
Abstract: The microstructural features of the tissue of long bones subjected to different biomechanical stresses could be a helpful tool for a better understanding of locomotor behavior in extant and extinct mammals, including equids. However, few researches have attempted to describe the bone tissue of extinct horses. In our study, we analyze and compare the histomorphometric features of the bone tissue in extant modern horses, Equus caballus, and Equus namadicus, a Pleistocene Indian extinct wild horse. The number, position, and size of the osteons and Haversian canals of the bone tissue, classifiable as dense Haversian tissue, were considered for the comparison. The results obtained highlight some differences between the analyzed species, E. caballus having fewer and bigger osteons than E. namadicus . The microstructural differences may depend on the different lifestyles and environmental conditions characterizing the two species. The results obtained suggest that comparing the biomechanical properties of extinct and modern horse species may provide indirect information on their paleoenvironment.